A Mendelian randomization study reveals a causal association between NASH and the risk of atrial fibrillation - Cheng, Biwei; Su, Xuekang; He, Jue; Gu, Yanghui; Chen, Mingtai; Wei, Yi; Yi, Yumeng; Chen, Peiying; Lin, Xiaojuan; Li, Tao; Xu, Chong; Liu, Qiang; et al. (Frontiers in Endocrinology, 2025)
BackgroundEpidemiological evidence suggests that non-alcoholic fatty liver disease (NAFLD) may increase the risk of atrial fibrillation (AF). However, the findings are inconsistent, and the causality remains to be established.MethodsWe conducted two-step, two-sample Mendelian randomization (MR) analysis to assess the association between genetically predicted NAFLD (i.e. chronically elevated serum alanine aminotransferase levels [cALT], imaging-based and biopsy-confirmed NAFLD) and AF. Subsequently, we further performed Mendelian randomization to investigate the causal relationship between non-alcoholic steatohepatitis (NASH), a subtype of NAFLD, and AF. The inverse variance weighted (IVW) method was used as the primary approach to reveal the potential causation between the exposure and outcome.ResultsThere was no significant causal association between NAFLD diagnosed based on cALT, confirmed by imaging, or verified by biopsy, and an increased risk of atrial fibrillation. Furthermore, the results of the IVW method revealed a positive causal effect of NASH on AF (OR=1.113, 95% CI=1.025-1.209, P = 0.011). In the reverse analysis, however, no evidence supported a significant genetic association between AF and NASH (OR=0.974, 95% CI=0.934-1.016, P = 0.214).ConclusionA causal relationship existed between NASH and the risk of AF. However, no significant genetic association has been observed between NAFLD and AF risk. This suggests that managing the progression of NAFLD may hold potential value in preventing the onset of AF.